Eksperimen Potensi Kain Serat Pisang Sebagai Material Produk Pelengkap Interior - Eko Prasetyo Kuslambang; Yusita Kusumarini; Filipus Priyo Suprobo (Intra, 2019)
Indonesia is a large tropical banana producing country. Nearly 50% of Asian banana is produced by Indonesia and its production continues to increase every year. Banana trees has great potential because all parts can be utilized, especially fibers in the midrib. Fronds from abaca banana (in Javanese called klutuk banana) can be woven into sheets of cloth. Bananas fiber in general is used as fashion material and fashion needs. Therefore, researchers are interested in conducting further experiments to look for other potential banana fiber fabrics as an interior complementary product. The experimental method was carried out by characteristic testing and fabric processing before being applied to complementary interior products.The experimental results show that banana fiber fabric with a composition of 50 banana fibers: 50 cotton fibers has the potential to be processed into interior complementary products. Banana fiber fabric needs to be coated with trikot cloth and felt cloth, then sewn with a technique of binding horizontal-vertical fibers. Recommendations for interior complementary products from banana fiber fabrics are backrest and seat stands, accessories, tablecloths, window covers, lamp shades, and partitions.